An Optimal Fuzzy High-Gain Observer for an Uncertain Nonlinear System. (4th April 2013) - Yu, Sung-Hoon; Kim, Yong-Tae; Park, Chang-Woo; Hyun, Chang-Ho
This paper proposes an alternative optimal fuzzy high-gain observer design scheme. The structure of the proposed observer is represented by the Takagi-Sugeno fuzzy model and has the integrator of the estimation error. It improves the performance of a high-gain observer and makes the observer robust against noisy measurements, uncertainties and parameter perturbation. The proposed observer adopts theH ∞ control technique and an adaptive projection algorithm. This technique results in a reduction of both the fuzzy approximation error and time-varying disturbances. In addition, the proposed observer accomplishes a fast transient response and parameter convergence. Some simulation results are given to present the validity of the theoretical derivations and the performance of the proposed observer.